2000
DOI: 10.1038/35024105
|View full text |Cite
|
Sign up to set email alerts
|

Pilus retraction powers bacterial twitching motility

Abstract: Twitching and social gliding motility allow many gram negative bacteria to crawl along surfaces, and are implicated in a wide range of biological functions. Type IV pili (Tfp) are required for twitching and social gliding, but the mechanism by which these filaments promote motility has remained enigmatic. Here we use laser tweezers to show that Tfp forcefully retract. Neisseria gonorrhoeae cells that produce Tfp actively crawl on a glass surface and form adherent microcolonies. When laser tweezers are used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
731
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 759 publications
(751 citation statements)
references
References 29 publications
16
731
0
4
Order By: Relevance
“…To initiate pilus assembly, the pilin subunit PilE, in its membrane bound state, is processed by the pre-pilin peptidase PilD, removing a short hydrophilic N-terminal peptide, and methylating the N-terminal amino acid (Nunn & Lory, 1991). Type IV pili are retractable, and this retraction process is responsible for the twitching motility of neisserial cells observed on solid media and mucosal epithelium (Merz et al, 2000). The cytoplasmic protein PilT is essential for retraction, but dispensable for pilus assembly (Wolfgang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…To initiate pilus assembly, the pilin subunit PilE, in its membrane bound state, is processed by the pre-pilin peptidase PilD, removing a short hydrophilic N-terminal peptide, and methylating the N-terminal amino acid (Nunn & Lory, 1991). Type IV pili are retractable, and this retraction process is responsible for the twitching motility of neisserial cells observed on solid media and mucosal epithelium (Merz et al, 2000). The cytoplasmic protein PilT is essential for retraction, but dispensable for pilus assembly (Wolfgang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of conditional double-knockout mutants has allowed the dissection of type IV pilus formation into three different phases -pilin processing, pilus formation and pilus extrusion (Wolfgang et al, 1998(Wolfgang et al, , 2000. To reveal these phases, it was essential to inactivate PilT, a putative ATP-binding protein involved in pilus retraction (Merz et al, 2000). This protein seems to act in quality control by preventing fibre formation and, in turn, minimizing growth defects that may occur in the absence of essential biogenesis components.…”
Section: Introductionmentioning
confidence: 99%
“…M. xanthus TFP were seen under EM as polar filaments measuring 5-7 nm in diameter and 4-10 m in length (19). Previous studies have revealed that TFP-dependent surface motilities are achieved through TFP extension and attachment to an external substrate followed by retraction, which pulls the cells forward (20)(21)(22). Extracellular fibril material has been visualized under SEM as 30-to 50-nm-thick intercellular fibers (23) that form a mesh-like network surrounding the cell body (24).…”
mentioning
confidence: 99%